Development of various partners' capacities and raising of awareness of climate-smart sheep and goat production in Ethiopia - Getachew, Tesfaye; Belay, Berhanu; Rischkowsky, Barbara A.; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
To increase the accessibility of climate-smart sheep and goat breeding and integrated interventions, a variety of training and awareness-raising activities were conducted throughout Ethiopia. The events are outlined in four chapters, with chapter 1 focusing on a training session on scaling up climate smart innovations that was held on April 19, 2022, with the intention of planning how to incorporate climate smart animal husbandry advancements into ongoing community-based breeding projects and introducing the CLEANED environmental assessment tool. There were 27 participants in total, including people from universities, research centers, and regional livestock offices. WOMBAT software and an introduction to the DTREO digital database were the main topics of Chapter 2, which was presented on May 18 and 19, 2022, at the GETVA hotel in Debre Berhan, Ethiopia. The training was organized by the International Center for Agricultural Research in the Dry Areas (ICARDA) team in Addis Ababa with financial support from the Accelerating the Impact of CGIAR Climate Research in Africa (AICCRA). A total of 34 participants from 29 Universities in Ethiopia, one from the Livestock Development Institute (LDI), one from Water and Land Resource Center (WLRC) and one from Debre Berhan Research centers and two from ICARDA. Two (6%) of the participants were women. Chapter three deal with training and awareness creation for various university partners including higher management bodies lecturers in animal and veterinary science, extension and development agents and community representative. The events were taking place at Wollo, Asosa, Jinka, Afar, Debre Berhan, Injibara and Mekdela Amba universities. A total of 350 were attended the event. Chapter four deal on awareness creation for research center directors and University presidents held at Capital Hotel in Addis Ababa on 16th November 2022 and 30th December 2022 respectively. A total of 11 research directors and 23 university presidents were attended the meeting. In summary, a total of 445 Participants from more than 11 research centers, 29 Universities, private sectors, development partners and extension office were attended the events. Researchers and university lecturers then returned to their original locations and educated more than 150 extension specialists and 1050 farmers to improve access to climate smart small ruminant innovations. CBBPs and integrated innovations were started and implemented more effectively as a result.